Nurses in Response to the Coronavirus: Pressures and Coping Mechanism from the Perspective of Nurses in Jordan - Alfawair, Salwa AbedAlhaleem Ahmad (Journal of Humanities & Social Sciences, 2022)
The aim of the study was to uncover the most visible pressure experienced by nurses under the Corona pandemic from their point of view and adaptation mechanism. The descriptive approach was used. The study tool was a questionnaire distributed to a sample of 48 nurses. Using the SPSS programme, the results of the study showed that the most significant type of pressure experienced by nurses was social pressure with an average calculation. (50.7) At the level of stress, the family compresses both parents and spouses and childrento a high degree of importance according to the arithmetic average. The physical pressure is followed by an average calculation of 42.3, followed byan economic pressure of 27.9. The study also revealed that the effective mechanism that helped nurses cope with the pandemic was to work with colleagues who were more experienced with the average of my account, 4 with a high degree of importance, and also virtual communication with the family with a high degree of importance at the average of my account (3.83). In the light of the findings, a series of recommendations and proposals were made to address these pressures.
Keywords: social pressure; corona virus; nurses; coping mechanism; Jordan